Synthesis and Crystal Structures of Nickel(II) and Cobalt(II) Complexes with 3-Methoxysalicylaldehyde Benzoylhydrazide - Zou, Li-Fei; Yang, Xiu-Yun; Wang, Dong-Xia; Gao, Ying; Wang, Yuan; Li, Yun-Hui (Asian Journal of Chemistry, 2012)
Two isostructural mononuclear complexes, [Ni(HL)(H2L)]·ClO4·1.5CH3OH (1) and [Co(HL)(H2L)]·ClO4·CH3CN·2H2O (2), have been synthesized (H2L = 3-methoxysalicylaldehyde benzoylhydrazide). In complexes 1 and 2, each metal atom is coordinated by four O atoms and two N atoms from two H2L ligands, forming a distorted octahedral coordination configuration. Additionally, in complex 1, the two neighboring molecules are found to form a centrosymmetric dimer through N (hydrazine)-H···O (phenolate/methoxyl) hydrogen bonds and the p-p stacking interactions between the two phenyl rings. The dimers are further constructed into an extended one dimensional chain structure through hydrogen bands. Unlike complex 1, complex 2 does not form dimer/chain but is rather a simple, discrete complex.